EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
The four papers in this issue address, in different ways, aspects of teachers’ role in education and curriculum. This issue of Journal of Research, Policy & Practice of Teachers & Teacher Education consists of papers contributed by scholars from various parts of the academic environment, from a teacher in a school to an international author from Nigeria. Between them, they raise important and emerging issues of teaching and teaching practices; the role of peace education (amuch talked about subject but very little written upon); managing curriculum in the primary school; the science acquisition skills of secondary school students and the declining interest in Islamic studies in schools in Nigeria.